Parallel computing with x10 - Murthy, Pvr (International Conference on Software Engineering 2008, 2008)
Many problems require parallel solutions and implementations and how to extract and specify parallelism has been the focus of Research during the last few decades. While there has been a significant progress in terms of (a)automatically deriving implicit parallelism from functional and logic programs, (b) using parallelizing compilers to extract parallelism from serial programs written in Fortran or C mainly by parallelizing loop constructs and (c) evolution of standards such as Message Passing Interface (MPI) to allow a Fortran or C programmer to decompose a problem into a parallel solution, the parallel computing problem is still not solved completely. With the emergence of parallel computing architectures based on multi-core chips, there is a need to rewrite existing software and also develop future software so that parallelism available at the hardware level is fully exploited.